REPRESENTATION OF WOMAN’S WISDOM IN ROBERT HERRICK’S POEM: THE LILY IN A CRYSTAL - SAFRIANSYAH, HILMY ADLAN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: poem, significance, sign, semiotics, superreader As a literary discourse, the conveyance context of a poem meanings and significances are mostly delivered implicitly by the poet. In a poem, implicitsignificance may contain double meanings that require deep understanding andfurther readings. Sometimes, implicit significance is conveyed by certain symbols. The selected approach to interpret this poem is semiotics theory by Michael Riffaterre. The focus of this research is finding the analysis result of a poem titled The Lily in a Crystal by using superreader semiotics approach that emphasizes on the reader’s ability to dissect particular poem.This poem, written by Robert Herrick, became one of the poems with the highest number of stanza in his book titled Hesperides. This poem contains the image of woman’s life. However, Robert Herrick illustrated it in unique connotations. The core message delivered in this poem is a wisdom. Problem of the study to be answered in this research is: what is the hidden message inside Robert Herrick’s poem entitled The Lily in a Crystal.In the superreader theory, there are three elements that must be answered inorder to interpret a poem, those are semiotics reading (heuristic and hermeneutic), the matrix, model, and variants, as well as hypogram. The result of this semiotics analysis based on Riffaterre shows the religious representation that is hidden in each word, which is the essence of this poem. The connotation words are dedicated to woman and her actions. A wisdom is the main  thing to face love that contains pleasure with sadness at once and lot of  temptations within. This poem is indirectly invites all woman who reads, because the word‘you’ in this poem is aimed for the position of a woman. The Matrix in this poem are wisdom and religiosity. From those matrix, it can be found that the main theme of this poem is about religiosity that deals with woman’s wisdom.